Muscle fibre conduction velocity in the vastus lateralis and medialis muscles of soccer players after ACL reconstruction - Nuccio, S.; Del Vecchio, A.; Casolo, A.; Labanca, L.; Rocchi, J. E.; Felici, F.; Macaluso, A.; Mariani, P. P.; Falla, D.; Farina, D.; Sbriccoli, P. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The neural factors underlying the persistency of quadriceps weakness after anterior cruciate ligament reconstruction (ACLR) have been only partially explained. This study examined muscle fiber conduction velocity (MFCV) as an indirect parameter of motor unit recruitment strategies in the vastus lateralis (VL) and medialis (VM) muscles of soccer players with ACLR. High-density surface electromyography (HDsEMG) was acquired from VL and VM in nine soccer players (22.7 ± 2.9 years; BMI: 22.08 ± 1.72 kg·m-2; 7.7 ± 2.2 months post-surgery). Voluntary muscle force and the relative myoelectrical activity from the reconstructed and contralateral sides were recorded during linearly increasing isometric knee extension contractions up to 70% of maximal voluntary isometric force (MVIF). The relation of MFCV and force was examined by linear regression analysis at the individual subject level. The initial (Intercept), peak (MFCV70) and rate of change (slope) of MFCV related to force were compared between limbs and muscles. The MVIF was lower in the reconstructed side than in the contralateral side (-%20.5; P<0.05 ). MFCV intercept was similar among limbs and muscles (P>0.05 ). MFCV70 and MFCV slope were lower in the reconstructed side compared to the contralateral for both VL (-28.5%, -10.1%, respectively; P<0.001 ) and VM (-22.6%, -8.1%, respectively; P<0.001 ). The slope of MFCV was lower in the VL than VM, but only in the reconstructed side (-12.4%; P<0.001 ). These results suggest possible impairments in recruitment strategies of high-threshold motor units (HTMUs) as well as deficits in sarcolemmal excitability, fibre diameter and discharge rate of knee extensor muscles following ACLR.